Not the Stereotypical Wilson Disease: A Case Report. Issue 1 (29th October 2021) - Datta, Amlan Kusum; Mukherjee, Adreesh; Chaudhuri, Jasodhara; Pandit, Alak; Gangopadhyay, Goutam
Background: Wilson disease (WD), a potentially treatable genetic disorder with perturbations in copper metabolism, presents with hepatic and neuropsychiatric manifestations. Both hyper and hypokinetic movements predominate the latter spectrum. Motor stereotypies, however, are exceedingly rare. Case Report: We present a case of a 12-year-old girl, with progressive behavioural alterations and cognitive impairment, with motor stereotypies involving the upper limbs, as the dominant movement semiology. She was diagnosed as WD with evidence of striatal involvement on brain imaging. Her motor symptoms partially responded to chelation therapy. Discussion: There are about five documented cases of motor stereotypies in WD worldwide, with only one being previously reported from India.